2022
DOI: 10.1111/dom.14719
|View full text |Cite
|
Sign up to set email alerts
|

Positive allosteric γ‐aminobutyric acid type A receptor modulation prevents lipotoxicity‐induced injury in hepatocytesin vitro

Abstract: Aim: To determine if a novel positive allosteric modulator of the γ-aminobutyric acid type A (GABA A ) receptor, the thioacrylamide-derivative HK4, which does not penetrate the blood-brain barrier, protects human hepatocytes against lipotoxicityinduced injury.Materials and Methods: Allosteric modulation of the GABA A receptor by HK4 was determined by patch clamp in HEK-293 cells, calcium influx in INS-1E cells and by using the specific GABA A channel blockers picrotoxin and tert-butylbicyclophosphorothionate (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
6
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 50 publications
3
6
0
Order By: Relevance
“…Substantial evidence supports that activation of the transcription factor NF-κB and downstream inflammatory signalling pathways are involved in hepatic insulin resistance (Tilg et al, 2017). In line, upregulated NF-κB gene expression in PA-treated HepG2 cells compared to untreated (p = 0.004) or PA and HK4-cotreated cells (p = 0.089) fits with protein expression analysis of our previous study (Rohbeck et al, 2022). Also in line with our previous study, the current data indicate an involvement of STAT signaling, since STAT5A is differentially expressed in our dataset.…”
Section: The Upstream Regulators Syvn1 and Tp53 Control And Integrate...supporting
confidence: 92%
See 4 more Smart Citations
“…Substantial evidence supports that activation of the transcription factor NF-κB and downstream inflammatory signalling pathways are involved in hepatic insulin resistance (Tilg et al, 2017). In line, upregulated NF-κB gene expression in PA-treated HepG2 cells compared to untreated (p = 0.004) or PA and HK4-cotreated cells (p = 0.089) fits with protein expression analysis of our previous study (Rohbeck et al, 2022). Also in line with our previous study, the current data indicate an involvement of STAT signaling, since STAT5A is differentially expressed in our dataset.…”
Section: The Upstream Regulators Syvn1 and Tp53 Control And Integrate...supporting
confidence: 92%
“…Therefore, we aimed to determine if the positive allosteric modulator (PAM) of the GABA A receptor, HK4, could prevent the deleterious effects of lipotoxicity in hepatocytes. In our recent publication ( Rohbeck et al, 2022 ) we were able to confirm the presence of the GABA A receptor in HepG2, as described by Minuk and colleagues ( Minuk et al, 1987 ; Rohbeck et al, 2022 ). Moreover, we showed that the GABA A receptor PAM, HK4, could reduce palmitate (PA)-induced DNA fragmentation, inflammation, cell death and especially apoptosis, in vitro ( Rohbeck et al, 2022 ).…”
Section: Introductionsupporting
confidence: 66%
See 3 more Smart Citations